Analisis Perilaku Biaya Dan Pengaruhnya Terhadap Profitabilitas Perusahaan Developer (Studi Kasus Perusahaan Developer di Sidoarjo) - Dian Fahrian (Universitas Nahdlatul Ulama Sidoarjo, 2020)
This research was conducted at the construction company developer PT Tiga Sinar Kreasindo (TSK) Sidoarjo. The purpose of this study was to determine the effect of cost behavior, fixed costs, variable costs, and semi-variable costs on company profitability consisting of ROA, ROE and NPM. The data used the company's financial statement data in 2018. This study used a descriptive analysis method, with a total of 30 respondents and using the Special for Statistics Science (SPSS) software. The results showed the influence of cost behavior, fixed costs, variable costs and semi-variable costs have a significant influence on company profitability.